KOMPETENSI, DISIPLIN KERJA DAN BUDAYA KERJA PENGARUHNYA TERHADAP KINERJA PEGAWAI - Yuniarto Rahmad Satato; Bima Prahar Adilase; Ganda Subrata (Lembaga Pengembangan Kinerja Dosen, 2022)
This research was conducted in the sub-district office in Demak Regency which aims to determine the effect of competence, work discipline and work culture on employee performance in the sub-district of Demak Regency. The research data was obtained through questionnaires and interviews. The sample used in this study was 60 respondents. The results of the study are expected to provide useful information for leaders and employees. The data obtained were processed using descriptive analysis and quantitative statistical analysis. Quantitative analysis uses regression analysis to determine the effect of the independent variable on the dependent variable, but before the test is carried out, the validity and reliability tests are carried out first and the requirements test. The results of the regression analysis show that competence, work discipline and work culture have a positive and significant impact on employee performance at sub-districts in Demak Regency.